التحديات التي تواجه الطواقم الطبية الفلسطينية في ظل الاعتداءات الصهيونية: دراسة قانونية تحليلية: The challenges facing the Palestinian medical staff in light of the Zionist attacks: An analytical legal study - Abu Oun, Mohammed Awni (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تُؤدي الطواقم الطبية الفلسطينية جهودا مهمة في مسيرة نضال الشعب الفلسطيني في مواجهة آلة الحرب والإجرام الإسرائيلية، وقد تعرضت هذه الطواقم خلال مسيرتها للكثير من الاعتداءات التي كلفتها عددا كبيرا من الشهداء والمصابين، إضافة إلى خسائر بليغة في المؤسسات والمنشآت الطبية. جاءت هذه الدراسة في ثلاثة مطالب رئيسية. إذ تناول المطلب الأول حماية الطواقم الطبية في القانون الدولي، ورصد المطلب الثاني أهم المحطات التي برز فيها دور الطواقم الطبية في مسيرة النضال الفلسطيني، فيما كشف المطلب الثالث عن أنواع وأشكال وبعض أرقام الانتهاكات الإسرائيلية بحق الطواقم الطبية الفلسطينية. وقد انتهجت الدراسة المنهج المسحي. خرجت الدراسة بعدد من النتائج جاء على رأسها تأكيد أهمية ومكانة الطواقم الطبية الفلسطينية واعتبار دورها جزءا مهما من العمل الوطني الفلسطيني، وقيام الاحتلال بانتهاكات واسعة ومتنوعة ضد هذه الطواقم دون حساب أو عقاب، كما أوصت الدراسة بعدد من التوصيات لعل أهمها، ضرورة دعم الطواقم الطبية وجهودها في خدمة الشعب الفلسطيني، وضرورة فضح جرائم الاحتلال بحقها، ووجوب بناء كيان إسلامي يمثل مرجعية تنظيمية على مستوى دول العالم الإسلامي من أجل ملاحقة الاحتلال قانونيا في المؤسسات الدولية ومحاسبته على تجاوزاته الإجرامية. Abstract The Palestinian medical crews exert great efforts in serving the Palestinians in their path of struggle against the Israeli occupation’s criminality and arbitrariness. For so long, they have been subjected to several Israeli attacks that costed them a large number of martyrs and causalities as well as huge damages to medical institutes and constructions. Basically, this study determines three main claims; the Protection of Medical Crews according to the International Law, the Prominent Stations that Highlighted the Role of Medical Crews in the Palestinians’ Path of Struggle, and Sorts, Shapes and Statistics of Israeli Violations against the Palestinian Medical Crews. The researcher used the descriptive analysis approach. Moreover, the study came up with several results. Most importantly, confirming the importance of the position of the Palestinian medical crews and considering them as a vital part of the Palestinian national work and emphasizing that the Israeli occupation committed diverse arbitrary violations against those crews with impunity. Finally, it recommends that the medical crews must be supported so they can keep serving the Palestinians, the Israeli crimes against the medical crews must be exposed, and an Islamic body representing an organizational baseline at the level of the Islamic nations must be built in order to legally prosecute and hold the Israeli occupation accountable before the international courts.